hsp72, a Host Determinant of Measles Virus Neurovirulence - Carsillo, Thomas (American Society for Microbiology, 2006)
Transient hyperthermia such as that experienced during febrile episodes increases expression of the major inducible 70-kDa heat shock protein (hsp72). Despite the relevance of febrile episodes to viral pathogenesis and the multiple in vitro roles of heat shock proteins in viral replication and gene expression, the in vivo significance of virus-heat shock protein interactions is unknown. The present work determined the in vivo relationship between hsp72 levels and neurovirulence of an hsp72-responsive virus using the mouse model of measles virus (MV) encephalitis. Transgenic C57BL/6 mice were created to constitutively overexpress hsp72 in neurons, and these mice were inoculated intracranially with Edmonston MV (Ed MV) at 42 h of age. The mean viral RNA burden in brain was approximately 2 orders of magnitude higher in transgenic animals than in nontransgenic animals 2 to 4 weeks postinfection, and this increased burden was associated with a fivefold increase in mortality. Mice were also challenged with an Ed MV variant exhibiting an attenuated in vitro response to hsp72-dependent stimulation of viral transcription (Ed N-522D). This virus exhibited an attenuated neuropathogenicity in transgenic mice, where mortality and viral RNA burdens were not significantly different from nontransgenic mice infected with either Ed N-522D or parent Ed MV. Collectively, these results indicate that hsp72 levels can serve as a host determinant of viral neurovirulence in C57BL/6 mice, reflecting the direct influence of hsp72 on viral gene expression.